A revision of the genus Rosapha Walker (Diptera: Stratiomyidae) - Kovac, Damir; Rozkošný, Rudolf (Zootaxa, 2012)
The species of Rosapha Walker, 1859 are revised and the monotypic genus Rosaphula Frey, 1934 is proposed as a newsynonym of Rosapha. Eleven species of Rosapha are distinguished and four of them, R. brevispinosa sp. nov. from Laosand Thailand, R. flavipes sp. nov. and R. stigmatica sp. nov. from Thailand, and R. flavistigmatica sp. nov. from India andMalaysia, are described as new. Rosapha bicolor Bigot, 1877 is proposed as a synonym of R. habilis Walker, 1859 on thebasis of type comparison. The males of R. handschini (Frey, 1934), R. obscurata de Meijere, 1916, and R. variegata deMeijere, 1919, are described for the first time. The distribution of ten species is probably confined to the Oriental Regionbut R. umbripennis Lindner, 1957, was described from New Guinea. Rosapha bimaculata Wulp in de Meijere, 1904, wasnewly recorded from India, Laos, Malaysia, Thailand and Vietnam, R. flagellicornis Enderlein, 1914, from Malaysia, R.obscurata from the Philippines and Thailand, and R. variegata from Indonesia (Sumatra), Malaysia, the Philippines, Thailand and Vietnam. A key to the Rosapha species is presented.